1993
DOI: 10.1182/blood.v81.10.2658.2658
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic difference of normal plasma cells from mature myeloma cells

Abstract: We have recently shown that two-color analysis with fluorescein isothiocyanate (FITC)-anti-CD38 antibody could clearly distinguish myeloma cells (plasma cells) from other hematopoietic cells in the bone marrow. Myeloma cells (plasma cells) alone were located at CD38strong positive (++) fractions. To further distinguish normal plasma cells from mature myeloma cells phenotypically, we examined immunophenotypes of normal plasma cells and myeloma cells by two-color flow cytometry with FITC-anti-CD38 antibody and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
1
7

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(121 citation statements)
references
References 0 publications
13
100
1
7
Order By: Relevance
“…3 CD19 has also been detected by flow cytometry in plasma cells isolated from human tissues. 6 Previous studies of CD19 in B-cell neoplasia have been limited to flow cytometric analysis of living cells 2,7-10 and its expression in B-cell neoplasia in routine tissue biopsy specimens has not been previously investigated. In this paper, we describe a polyclonal antibody against CD19 that is reactive on paraffin sections.…”
Section: Introductionmentioning
confidence: 99%
“…3 CD19 has also been detected by flow cytometry in plasma cells isolated from human tissues. 6 Previous studies of CD19 in B-cell neoplasia have been limited to flow cytometric analysis of living cells 2,7-10 and its expression in B-cell neoplasia in routine tissue biopsy specimens has not been previously investigated. In this paper, we describe a polyclonal antibody against CD19 that is reactive on paraffin sections.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, anti-CD56 began to be used for characterization and differentiation of normal and neoplastic plasma cells using phenotypic analysis. [10][11][12] A recent study 13 found that expression of NCAM in myeloma cells is as strong as in the osteoblast layer and is associated with lytic bone lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow monoclonal cells (BMMNC) from BM aspirates were separated by Ficoll-Hypaque centrifugation, suspended at a concentration of 0.5 · 10 6 cells ⁄ mL, and cultured in RPMI-1640 medium supplemented with 10% FBS (M.A. Bioproducts, Walkersville, MD, USA) as reported previously (20).…”
Section: Isolation Of Bone Marrow Mononuclear Cells From Mgus and Myementioning
confidence: 99%
“…Cells were stained with fluorescein isothiocyanate (FITC)-labeled anti-CD38 (A07778, Beckman Coulter, Tokyo, Japan), phycoerythrin (PE)-labeled anti-mature plasma cell-1 (MPC-1) [Japan Immunoresearch Laboratories (JIMRO), Takasaki, Japan], PE-labeled anti-CD19 (A07769, Beckman Coulter) antibody, PE-anti-CD54 antibody (IM1239U; Beckman Coulter, Hialeah, FL, USA), or PE-labeled anti-human CXCR4 (FAB170P; R&D Systems, Minneapolis, MN, USA). Cells were washed twice with phosphate-buffered saline containing 1% FBS, incubated at 4°C for 30 min with the above antibodies, and analyzed by a flow cytometer (Epics Elite ESP; Beckman Coulter) (20). The cells were also sorted by the cell sorter (Epics Elite ESP) as reported previously (20).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation